Sugarcane bagasse ash as fertilizer for soybeans: Effects of added residues on ash composition, mineralogy, phosphorus extractability and plant availability - Dombinov, Vitalij; Herzel, Hannes; Meiller, Martin; Müller, Felix; Willbold, Sabine; Zang, Joachim W.; da Fonseca-Zang, Warde A.; Adam, Christian; Klose, Holger; Poorter, Hendrik; Jablonowski, Nicolai D.; Schrey, Silvia D. (Frontiers in Plant Science, 2022)
Sugarcane bagasse is commonly combusted to generate energy. Unfortunately, recycling strategies rarely consider the resulting ash as a potential fertilizer. To evaluate this recycling strategy for a sustainable circular economy, we characterized bagasse ash as a fertilizer and measured the effects of co-gasification and co-combustion of bagasse with either chicken manure or sewage sludge: on the phosphorus (P) mass fraction, P-extractability, and mineral P phases. Furthermore, we investigated the ashes as fertilizer for soybeans under greenhouse conditions. All methods in combination are reliable indicators helping to assess and predict P availability from ashes to soybeans. The fertilizer efficiency of pure bagasse ash increased with the ash amount supplied to the substrate. Nevertheless, it was not as effective as fertilization with triple-superphosphate and K2SO4, which we attributed to lower P availability. Co-gasification and co-combustion increased the P mass fraction in all bagasse-based ashes, but its extractability and availability to soybeans increased only when co-processed with chicken manure, because it enabled the formation of readily available Ca-alkali phosphates. Therefore, we recommend co-combusting biomass with alkali-rich residues to increase the availability of P from the ash to plants.